Clinical Efficacy of the Use of Honey as Wound Treatment in Surgical Site Infection due to Hysterectomy Patient with Type 2 Diabetes Mellitus - Hartati; Mufida Muzakkie; Yusuf Effendi; Ferry Yusrizal; Ramzi Amin; Cindy Kesty; Vicela Patricia Virgyna (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Honey is believed to be used in the topical treatment of wounds and burns due to its anti-bacterial and wound healing promotion activities. The sugar content in honey is high enough to inhibit microbial growth. This case report reports the clinical efficacy of using honey as a postoperative hysterectomy wound dressing with type 2 diabetes mellitus complications. Case Presentation: A woman, 40 years old, lived in Palembang, housewife, came with complaints of open surgical scars and smelling pus. The patient is a postoperative patient with cesarean section with indications of a prolonged latent phase and macrosomia. The patient also had a history of uncontrolled diabetes mellitus since 8 years ago. Intraoperatively, a wound dehiscence is obtained in the lower uterine segment and adhesions between the anterior uterine body and the omentum and transverse colon. The patient finally underwent a supracervical hysterectomy and the surgical secretions were examined for bacterial culture and antibiotic resistance. During wound care, the patient's surgical wound was treated using honey dressings. Patient experienced improvement after treatment for 12 days post-operation. Conclusion: Honey has antibacterial and tissue regeneration ability which is high enough to heal surgical wounds. Further studies are needed for the application of honey to postoperative wounds more widely